Analisis Yuridis Pelaksanaan Peradilan Koneksitas Dalam Hukum Acara Peradilan Militer di Indonesia - Diva Pramesti Islami; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The ability of general courts to try cases involving crimes committed by both military personnel and civilians is an exception or deviation from the rule that a person must be tried in every court. Articles 3 and 4 of Law Number 5 of 1950 which regulate the authority of military justice and are linked to the topic of criminal acts (crimes and violations), give us a glimpse of the importance of the relationship. In general, general provisions apply to all cases handled jointly by military courts that can be justified and military courts that cannot be justified, unless there are special requirements. For example, losses caused by illegal activities would be more appropriately handled through military justice, provided that the Supreme Court has given its approval for the case to be tried in a military court